Faktor-Faktor Yang Mempengaruhi Nilai Perusahaan: Kualitas Audit, Pengungkapan Sukarela, Dan Profitabilitas - Dani Iwan Saputra; Cris Kuntadi (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2024)
This article aims to determine factors that can influence company value such as audit quality, voluntary disclosure, and profitability through a literature review. This article reviews the factors that influence company value, namely audit quality, voluntary disclosure, and profitability, an auditing literature study. The purpose of this article is to develop hypotheses regarding the relationships between variables for use in future research. The findings of this literature review article are: 1) Company value is influenced by audit quality; 2) Company value is influenced by voluntary disclosure; and 3) Company value is influenced by profitability.